Stress and Burnout in EFL Teachers: The Mediator Role of Self-Efficacy - Chang, Heli (Frontiers in Psychology, 2022)
Within the class environment, particularly in the language learning setting, stress is considered to be the most common mental condition educators experience in their work, and due to the effect of stress on teachers, burnout similarly occurs because EFL teachers periodically experience affective trauma while participating and engaging in their careers. To solve the problem, one must consider teacher self-efficacy, a significant construct that can mitigate the probability of burnout by preventing the occurrence of stress at work that also plays a key role in enhancing positive upshots. To emphasize the impact of teachers’ stress and burnout on the one hand and the mediator role of teachers’ efficacy, on the other hand, this mini-review attempted to study the issue. Finally, some scholastic recommendations are pinpointed.